A Companion to Greeks Across the Ancient World - De Angelis, Franco (Blackwell Companions to the Ancient World Ser, 2020)
Cover -- Title Page -- Copyright Page -- Contents -- Maps -- Illustrations and Tables -- Abbreviations -- Notes on Contributors -- Acknowledgments -- Introduction: Greeks across the Ancient World -- Notes -- References -- Part I Approaches, Ancient and Modern -- Chapter 1 Mobility in the Ancient Greek World: Diversity of Causes, Variety of Vocabularies1 -- Categories of Mobility -- Mass Mobility -- Forced Migrations of Populations -- Personal Mobility -- Conclusion -- Notes -- References -- Chapter 2 English-Speaking Traditions and the Study of the Ancient Greeks outside their Homelands -- Motherlands, Colonies, and the Marginalization of Greeks on the Margins -- Apoikiai, Emporia, and the Polis -- Greeks and Non-Greeks -- Conclusion -- Note -- References -- Chapter 3 French-Speaking Traditions and the Study of Ancient Greeks outside their Homelands1 -- The Century When it all Began -- Victor and Jean Bérard, from the Sea to the Earth -- Ceramics and Commerce -- Southern France: The Birth of a Field Laboratory -- Roland Martin and Urban Spaces -- Between Apoikiai and Emporia -- Territories -- A History of Style -- Conclusion -- Note -- References -- Chapter 4 German-speaking Traditions (including the Habsburg Empire) and the Study of the Ancient Greeks outside their Homelands -- Changing Perspectives on "Colonization" -- The "Greek" People/Race/State(s)/Nation(s) -- Overpopulation versus Trade -- Texts and Pots -- A Postcolonial Epilogue -- Notes -- References -- Chapter 5 Italian-Speaking Traditions and the Study of the Ancient Greeks outside their Homelands -- Pre-unification Italy: Monarchies and Invasions -- Nationalism 1861-1945: The Rise and Fall of Ancient Rome -- The Postwar Internationalism: Greeks as Olive Branch? -- Conclusions -- References.